A new species of Camaenidae (Gastropoda, Pulmonata) from Nusa Penida and Lombok Islands, Indonesia: novelty in a well-known fauna. (2nd January 2018) - Páll-Gergely, Barna; Otani, Jamen Uiriamu; Hosoda, Takashi; Asami, Takahiro; Harl, Josef
ABSTRACT: A new species of camaenid land snail, Vulnus wallacei Páll-Gergely, Otani & Hosoda n. sp. is described from Nusa Penida and Lombok Islands, Indonesia. The new species is putatively classified into the genus Vulnus, which is only known so far from the Northern Maluku Islands. The genital anatomy, especially the presence of a well-developed penial sheath in V. wallacei, suggests a close relationship with Australian camaenids. However, the molecular phylogeny based on partial cytochrome c oxidase I, and 16S and 28S ribosomal RNA genes shows that the new species falls outside the cluster of all Australian Camaenidae. http://www.zoobank.org/urn:lsid:zoobank.org:pub:D28554D0-3578-4E95-8849-09EAFB7D30F7